Island of Graves - McMann, Lisa (McMann, Lisa. Unwanteds, 2015)
Everything Aaron has worked so hard to build in Quill has crumbled. Fallen from the height of power and influence and left for dead in a foreign place, Aaron has lost everything, and now he must humbly beg for food from those who saved his life. In Artime, Alex chooses his people over his brother and abandons his search for Aaron, closing the door on that relationship forever. The Artimeans need his focus now more than ever as they face the terrifying power of a new enemy who has taken control of Quill the notoriously evil Gondoleery Rattrapp.